The Effect of Interactive PowerPoint Media and Learning Motivation on Social Studies Learning Outcomes Among Elementary Students - Erinawati Erinawati; Alfroki Martha; Weni Yulastri (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2026)
The quality of social studies learning at the elementary school level remains a concern, particularly regarding the limited use of innovative media and students' low intrinsic motivation. This study aimed to examine the effect of interactive PowerPoint media and learning motivation—both individually and simultaneously—on the social studies learning outcomes of fifth-grade students. A quantitative approach with an ex post facto design was employed. The subjects were 151 fifth-grade students selected through proportional random sampling from a population of 243 students across nine public elementary schools in Siulak Mukai District. Data were collected through questionnaires and analyzed using multiple linear regression, the coefficient of determination, t-tests, and F-tests. The results revealed that interactive PowerPoint media had a significant positive effect on learning outcomes (t = 4.23, p = 0.001, Cohen's d = 0.68), as did learning motivation (t = 3.87, p = 0.002, Cohen's d = 0.61). Simultaneously, both variables significantly predicted learning outcomes (F = 18.74, p < 0.001), accounting for 62.3% of the variance in learning outcomes (R² = 0.623). These findings suggest that elementary school teachers should systematically integrate interactive PowerPoint media into social studies instruction while concurrently implementing motivation-enhancing strategies—such as immediate feedback, goal-setting activities, and contextually relevant content presentation—to sustainably optimize student learning outcomes.